Optimal zero forcing precoder and decoder design for multi-user MIMO FBMC under strong channel selectivity - Rottenberg, Francois; Mestre, Xavier; Louveaux, Jerome (Proceedings of the ... IEEE International Conference on Acoustics, Speech and Signal Processing (1998), 2016)
This paper investigates the optimal design of precoders or decoders under a channel inversion criterion for multi-user (MU) MIMO filterbank multicarrier (FBMC) modulations. The base station (BS) is assumed to use a single tap precoding/decoding matrix at each subcarrier in the downlink/uplink, resulting in a low complexity of implementation. The expression of the asymptotic mean squared error (MSE) for this precoding/decoding design in the case of strong channel selectivity is recalled and simplified. Optimizing the MSE under a channel inversion constraint, the expression of the optimal precoding/decoding matrix is found. It is shown that as long as the number of BS antennas is larger than the number of users, the optimized precoder and decoder can compensate for the channel frequency selectivity and even restore the system orthogonality for a large enough number of BS antennas.